Toxicological Effects of Glufosinate-Ammonium-Containing Commercial Formulations on Biomphalaria glabrata in Aquatic Environments: A Multidimensional Study from Embryotoxicity to Histopathology - Yuncheng Qian; Jialu Xu; Yilu Feng; Ruiqi Weng; Keda Chen; Hezheng Zheng; Xianwei Li; Qingzhi Zhao; Xiaofen Zhang; Hongyu Li (Toxics, 2025)
Glufosinate-ammonium (GLA) is a broad-spectrum herbicide widely used for weed control. However, its potential toxic effects on non-target aquatic organisms, especially in freshwater ecosystems, are of growing concern. This study investigates the toxic effects of GLA on Biomphalaria glabrata, a freshwater snail highly sensitive to environmental pollutants and commonly used as a model organism in toxicological studies. Acute toxicity tests revealed that the 96-h LC50 of GLA for adult snails was 3.77 mg/L, indicating moderate toxicity, while the LC50 for embryos was 0.01576 mg/L, indicating extremely high toxicity. Chronic exposure experiments further showed that at high concentrations (0.5 mg/L), the shell diameter and body weight of the snails not only failed to increase but also decreased, and they ceased to lay eggs. Moreover, their hepatopancreas and gonads suffered significant damage. Even at an environmentally relevant concentration of 0.05 mg/L, the body length, body weight, and reproductive capacity of the snails were inhibited, and damage to the hepatopancreas and gonads was observed. These findings provide important data for assessing the potential risks of GLA to aquatic ecosystems and offer a scientific basis for formulating environmental protection policies and optimizing herbicide usage standards.